PENGUKURAN INFRASTRUKTUR DRAINASE PERMUKIMAN DI KELURAHAN LEATO UTARA UNTUK MENDUKUNG SANITASI LINGKUNGAN YANG LAYAK - Imran, Mohammad; Idris, Nur Oktavin; Katili, Andi Yusuf (Universitas Bina Taruna Gorontalo, 2024)
Drainage infrastructure of adequate is an important component in supporting proper environmental sanitation, especially in coastal settlements area such as Leato Utara Village. This activity aims to measure the existing condition of the residential drainage channels behind the Babussa'adah Mosque in RW 1 Leato Utara Village, Dumbo Raya District, Gorontalo City, analyze the measurement results and provide recommendations for improvement in the form of drainage channel planning/rehabilitation design. The methods used include socialization, mapping and measuring drainage infrastructure. The results show that the condition of the drainage channels is experiencing sedimentation, blockages, and physical damage. This condition causes waterlogging, environmental pollution, and health risks. The output of this activity is to raise awareness among the community who use the drainage infrastructure so that they have an awareness of protecting the environment, not littering for proper environmental sanitation.